Bridging Competency and Performance: The Mediating Role of Technology in Professional Training and Emergency Preparedness - R. Rudi Alhampi; Syahrial Shaddiq; Rini Elfina; Sumandi Sumandi; Steven Kenli (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
The rapid advancement of technology has transformed workforce training and professional development, necessitating the integration of technology-driven learning models to enhance competency acquisition and professional readiness. This study examines the relationships between Training and Professional Development (TPD), Emergency Preparedness Competency (EPC), Effectiveness of Technology Implementation in Education and Training (ETIET), and Performance and Readiness of Educators/Professionals (PREP). Using a quantitative research design, data were collected from 70 employees at PT. Aginda Riau Abadi through a structured survey, and Structural Equation Modeling (SEM) with Smart PLS was employed for analysis. The findings indicate that TPD and EPC have significant direct effects on PREP, but their influence is stronger when mediated through ETIET, confirming the crucial role of technology in bridging training outcomes and professional performance. The results demonstrate that organizations that invest in VR-based simulations, AI-driven learning platforms, and interactive digital tools can significantly enhance workforce preparedness, crisis management skills, and overall performance. This study highlights the necessity of a blended learning approach that integrates competency-based training with technology-enhanced learning experiences, ensuring professionals are equipped with both theoretical knowledge and practical, technology-adaptive skills. Future research should explore longitudinal effects of technology-mediated training. Keywords: Training; Professional; Development; Emergency; Preparedness